(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2024)
The article is devoted to the development of the constitutional economy in the Republic of Belarus, as the most important element of which the author sees the social responsibility of subjects of legal relations. The idea of social responsibility significantly develops the theory and normative model of constitutional economics and strengthens the constitutional foundations for the continuous improvement of the social function of the state. The author draws attention to the fact that the implementation of the constitutional principle of social responsibility requires further scientific, normative and law enforcement activities to reveal its regulatory potential.